The Legal, Economic, Social, Criminal and Political Challenges of Video Piracy: The Nigerian Experience - Abdur-Raheem, Adeyemi Ridwan (2012)
In the circumstance of existing pragmatic problem of an endangering high prevalence of video piracy and dearth of empirical enquiries, this study attempted to fill the knowledge gap in the global video piracy discourse from the legal, ethical, moral, economic, criminal and political perspectives in Nigeria. The study investigated the challenges of video piracy in Nigeria from multiple perspectives. Adopting the qualitative design and the case study approach, a triangulation of the in-depth interview, focus group discussion and document analysis methods were used for data collection. While the judgment sampling method was adopted for information gathering from respondents, the interpretive and critical analytical methods were used for the data analysis. The study’s theoretical framework was the diffusion of innovation theory. A set of eight findings of this study which uniquely contribute to the body of knowledge on video piracy in Nigeria and globally include: the dangerous ethnic dimension of the video piracy trend in Lagos; the low level of awareness on video piracy amongst the Nigerian public; the poor level of monitoring of post production and reproduction processes by producers and right owners; the internal sabotage within production plants and among video marketers; poor financial and operational capacity of stakeholders, non usage of highly sophisticated technological devices to protect video works; the experience of devastating psychological trauma by video producers and marketers; unwilling resort of video producers to low quality production to reduce cost and risk; and finally, the four fundamental factors refuting the claim of video piracy’s contribution to the emergence and popularity of the Nigerian video industry. The significance of these findings includes: strategic insight and understanding of the video piracy dynamics capable of facilitating strategic planning; control; eradication of video piracy; strategic conflict prevention; knowledge update on video piracy and strategic economic and cultural development.